Involvement of Protein Kinase C α and δ Activities on the Induction of the Retinoic Acid System in Mammary Cancer Cells - Berardi, Damian Emilio (2014)
It has been established that retinoids exert some of their effects on cell differentiation and malignant phenotype reversion through the interaction with different members of the protein kinase C (PKC) family. Till nowadays the nature and extension of this interaction is not well understood. Due to the cytostatic and differentiating effects of retinoids, in the present study we propose to evaluate whether the crosstalk between the retinoid system and the PKC pathway could become a possible target for breast cancer treatment. We could determine that ATRA (all-trans retinoic) treatment showed a significant growth inhibition due to (G1 or G2) cell cycle arrest both in LM3 and SKBR3, a murine and human mammary cell line respectively. ATRA also induced a remarkable increase in PKCα and PKCδ expression and activity. Interestingly, the pharmacological inhibition of these two PKC isoforms prevented the activation of retinoic acid receptors (RARs) by ATRA, indicating that both PKC isoforms are required for RARs activation. Moreover, PKCδ inhibition also impaired ATRA-induced RARα translocation to the nucleus. In vivo assays revealed that a combined treatment using ATRA and PKCα inhibitors prevented lung metastatic dissemination in an additive way. Our results clearly indicate that ATRA modulates the expression and activity of different PKCs. Besides inducing cell arrest, the activity of both PKC is necessary for the induction of the retinoic acid system. The combined ATRA and PKCα inhibitors could be an option for the hormone-independent breast cancer treatment.